Financial Technology and Literacy Shaping Students' Financial Management with Digital Literacy: Fintech dan Literasi Keuangan Membentuk Perilaku Pengelolaan Keuangan Mahasiswa dengan Literasi Digital - Fadiyah, Nur Laily; Widodo, Heri (Indonesian Journal of Law and Economics Review, 2024)
Financial management behavior is crucial for students, particularly as they engage with evolving financial technologies. However, there is a limited understanding of how financial technology and financial literacy interact to shape financial behavior, especially when considering digital literacy as a moderating factor. This study addresses this knowledge gap by examining the roles of financial technology and financial literacy on students' financial management behavior, with digital literacy as a potential moderator. Using a quantitative research method, primary data were gathered through a questionnaire survey from a sample of 114 accounting students at Muhammadiyah University of Sidoarjo, class of 2020. The findings indicate a positive relationship between financial technology and financial literacy on financial management behavior. Furthermore, digital literacy was found to moderate the effect of financial technology, strengthening its influence on students' financial management behavior. However, digital literacy did not moderate the influence of financial literacy on financial management behavior. The novelty of this research lies in its exploration of digital literacy's role as a moderating variable. Implications suggest the importance of incorporating digital literacy into financial education programs to enhance students' financial management practices. Highlights: Positive Relationship: Financial technology and literacy improve students' financial management behavior. Moderating Role: Digital literacy strengthens the effect of financial technology on financial behavior. No Moderation: Digital literacy does not moderate the impact of financial literacy on behavior. Keywords: Financial Technology, Financial Literacy, Digital Literacy, Financial Management, Student Behavior